Perspectives on Electronic Data Processing: A Book of Readings. - Elliott, C. Orville; Spiller, Earl A. (The Accounting Review, 1973)
Abstract The article reviews the book "Perspectives on Electronic Data Processing: A Book of Readings," edited by James D. J. Holmes.